Improvement proposal for inventory management based on ddmrp in supply warehouse of a metal mechanical company - Gallegos Oliden, Ariel Sebastian (2025)
According to León & Torre (2016), in recent years the growth of the market and competitors in the industrial sector requires faster, more reliable dispatch at a lower price. As a result of this analysis, the design of an improvement proposal for the management of the supply warehouse of a metalworking company based on the DDMRP methodology was considered relevant. This improvement seeks to standardize the warehouse's operational processes and reduce the average inventory level. Likewise, the proposal was validated by simulating the normal warehouse flow in Python. At the conclusion of the study, it was demonstrated that the implementation of the tools described above allows a reduction in the inventory level of 6.23% and it was proven that the DDMRP methodology allows the implementation of an inventory management system that guarantees better control and visualization of the inventory of the warehouse.